Extremely Flexible Indium‐Gallium‐Zinc Oxide (IGZO) Based Electronic Devices Placed on an Ultrathin Poly(Methyl Methacrylate) (PMMA) Substrate. (31st May 2018) - Kumaresan, Yogeenth; Lee, Ryeri; Lim, Namsoo; Pak, Yusin; Kim, Hyeonghun; Kim, Woochul; Jung, Gun‐Young
Abstract: The flexibility of metal oxide‐based electronic devices is severely limited by the thickness of their substrate. To enhance the flexibility of semiconducting metal oxide‐based electronic devices, a new and simple way to fabricate indium‐gallium‐zinc oxide (IGZO)‐based electronic devices on an ultrathin (1.9 µm) poly(methyl methacrylate) (PMMA) substrate is introduced. The PMMA layer spin‐coated on an unmodified glass slide has no chemical interactions at the interface, resulting in weak adhesion. Therefore, the PMMA layer with the devices is readily peeled off the underlying glass slide without using any sacrificial layer. Thin film transistors (TFTs) and gas sensors are fabricated on a 1.9 µm thick PMMA substrate. The fabricated bottom‐gated IGZO TFTs exhibits excellent transistor performances with a mobility of 10.7 cm 2 V −1 s −1, a threshold voltage of 8.4 V and an on/off current ratio of 5 × 10 5 . The PMMA substrate having palladium (Pd)‐decorated IGZO H2 sensors is attached to the nonplanar substrates such as wrinkled hand glove and poly(vinyl chloride) (PVC) gas tubes, and the sensors demonstrate an excellent sensitivity of ≈10 6 % at 5% H2 concentration at room temperature. Furthermore, both electronic devices show superior flexibility without any performance degradation even at a bending radius down to <1 mm. Abstract : A novel approach for fabricating ultraflexible indium‐gallium‐zinc oxide‐based devices on ultrathin poly(methyl methacrylate) substrates is proposed. The devices, transistors and gas sensors, exhibit unprecedented flexibility down to a bending radius of <1 mm without any performance degradation and the sensors have a potential to be conformably attached to the fittings of containers or pipe lines to detect the leakage.